The Role of Viral Marketing and Content Marketing in Miniso Purchases on TikTok: Pengaruh Viral Marketing, Konten Marketing Dan Live Streaming Terhadap Keputusan Pembelian Melalui Brand Trust Pada Toko Miniso di Tik Tok - Agil Karisa; Ambarwati , Diana; Munawaroh, Nuril Aulia (Universitas Muhammadiyah Pontianak, 2026)
This study investigates the impact of viral marketing, content marketing, and live streaming on purchase decisions, with brand trust as a mediating variable, among TikTok users who shop at Miniso in Kediri. Using a quantitative approach with 384 respondents, data were analyzed via SEM-PLS. Results show that all three marketing strategies significantly affect brand trust and purchase decisions. However, brand trust only mediates the effects of viral marketing and live streaming. These findings highlight the importance of interactive, trust-building strategies on TikTok. Miniso should enhance brand trust through engaging content and consider expanding platforms and variables for future research.